Allelochemical of Archidendron jiringa Pods and Sorghum bicolor Biomass Extracts Combined with a Premixed Formulation of Atrazine and Mesotrione - Simarmata*, Marulak; Siahaan, Wendi; Prasetyo, Prasetyo; Marlin, Marlin (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2023)
The aim of this research was to evaluate the allelochemicals in jering pods and sorghum biomass extracts combined with premixed formulations of the herbicides, atrazine and mesotrione. The research was conducted in the laboratory and experimental field of the Department of Agronomy, University of Bengkulu, Indonesia, from December 2019 to July 2020. The allelochemicals in jering pods and sorghum biomass extracts and their combination with the herbicides were tested on seed germination, and weed control was tested on corn grown in polybags. The results showed that aqueous extracts of jering pods and sorghum biomass combined with the herbicide mixtures of atrazine and mesotrione did not inhibit the seed germination of corn but suppressed the length and the weight of the radicles and plumules. The study of the efficacy of jering pods and sorghum biomass extracts on the weeds (total of grasses and broadleaves) revealed that the two agents, when applied separately, suppressed weed biomass by 27 and 32%, respectively. When the two extracts were combined, their combined efficacy increased to 56%. Furthermore, the plant height, stem diameter, and corn stover weight increased with the allelochemicals and herbicide treatments. The cobs yield per plant increased from 19 to 22% with the separate application of the allelochemicals found in the jering pods and sorghum biomass, respectively, and from 27 to 34% when the allelochemicals were combined with the herbicides. This research provided a novel approach using the allelochemical extracts from jering pods and sorghum biomass as natural herbicides for weed control. Keywords: allelochemicals; herbicide combination; jering pods; sorghum biomass; weed control *Corresponding author: E- mail: marulak_simarmata@yahoo.com